A Chandra survey of z ≥ 4.5 quasars. Issue 2 (15th April 2021) - Li, Jiang-Tao; Wang, Feige; Yang, Jinyi; Bregman, Joel N; Fan, Xiaohui; Zhang, Yuchen
ABSTRACT: X-ray observations provide a unique probe of the accretion disc corona of supermassive black holes (SMBHs). In this paper, we present a uniform Chandra X-ray data analysis of a sample of 152 z ≥ 4.5 quasars. We firmly detect 46 quasars of this sample in 0.5–2 keV above 3σ and calculate the upper limits of the X-ray flux of the remaining. We also estimate the power-law photon index of the X-ray spectrum of 31 quasars. 24 of our sample quasars are detected in the FIRST or NVSS radio surveys; all of them are radio-loud. We statistically compare the X-ray properties of our z ≥ 4.5 quasars to other X-ray samples of active galactic nuclei (AGNs) at different redshifts. The relation between the rest-frame X-ray luminosity and other quasar parameters, such as the bolometric luminosity, UV luminosity, or SMBH mass, shows large scatters. These large scatters can be attributed to the narrow luminosity range at the highest redshift, the large measurement error based on relatively poor X-ray data, and the inclusion of radio-loud quasars in the sample. The L X – L UV relationship is significantly sublinear. We do not find a significant redshift evolution of the L X – L UV relation, expressed either in the slope of this relation, or the departure of individual AGNs from the best-fitting αOX – L UV relation (ΔαOX ). The median value of the X-ray photon index is Γ ≈ 1.79, which does not show redshift evolution from z = 0 to z ∼ 7. The X-ray and UV properties of the most distant quasars could potentially be used as a standard candle to constrain cosmological models. The large scatter of our sample on the Hubble diagram highlights the importance of future large unbiased deep X-ray and radio surveys in using quasars in cosmological studies.